Moral Values Addressed in Students' English Textbook 7th Grade 2013 Curriculum: A Textual Analysis - Mundarti, - (2015)
This article which is entitled "Moral Values Addressed in Students' English Textbook 7th Grade 2013 Curriculum: A Textual Analysis" aims to find out the integration of the moral values addressed in the tasks which are contained in the students' English textbook entitled "When English Rings a Bell(2014)". This study is conducted since this textbook serves as a fundamental source of teaching and learning process in 2013 curriculum. Moreover, empowering character in education is important since it is a base for students to live in the broader society. There are six moral values that should be integrated in all aspects of teaching and learning process. Those are responsibility, self-discipline, care, polite, self-confidence, and honesty. Those six moral values are integrated in the tasks which are contained in this textbook since it is developed by using task-based approach. Qualitative method equipped with textual analysis is employed to gather the data. The result is found in form of textual evidence. From the textual evidences, it can be concluded that those six moral values are integrated in the tasks. However, there are five chapters which do not have values expected